A new triterpenoid and other constituents from Lepidogrammitis drymoglossoides. (April 2015) - Zhang, Li-Yuan; Wang, Teng-Hua; Ren, Ling-Zhi; Wan, Ming-Zhu; Wu, Hui-Fei; Mei, Quan-Xi; Gao, You-Heng
Abstract: Phytochemical investigation of a Chinese fern Lepidogrammitis drymoglossoides led to the isolation of five compounds, including one triterpenoid, two lignans and two glycosides. Their structures were determined to be filic-3-ene-28-oic acid (1), (−)-syringaresinol-4 -O- beta-d -glucopyranoside (2), lyoniresinol (3), 4- O- beta-d -glucopyranosyl caffeic acid (4) and n -butyl- O- beta-d -fructopyranoside (5) on the basis of mass and NMR spectra and chemical and physical properties. Filic-3-ene-28-oic acid (1) is a new triterpenoid, while compounds 2–5 were isolated from the genus Lepidogrammitis for the first time. Chemotaxonomic significance of this investigation is summarized. Highlights: Chemical constituents of a Lepidogrammitis drymoglossoides are studied. We report one new triterpenoid (1), two lignans (2, 3) and two glycosides (4, 5). Compounds 2–5 are isolated from the genus Lepidogrammitis for the first time. Compounds 1–3, 5 might serve as chemotaxonomic markers within Polypodiaceae.